Ultrasound-guided posterior quadratus lumborum block can reduce postoperative opioid consumption and promote rapid recovery in patients undergoing sutureless laparoscopic partial nephrectomy: A triple-blind, randomized, controlled study - Zhu, Youzhuang; Li, Zhichao; Qin, Shangyuan; Xu, Hao; He, Jianshuai; Sheng, Fang; Zhao, Qin; Kang, Yihan; Gao, Xin; Li, Si; Chai, Jun; Chen, Lina; et al. (Frontiers in Oncology, 2022)
Study objective Our hypothesis was that posterior quadratus lumborum block in the context of multimodal analgesia will reduce postoperative opioid consumption and improve the quality of recovery in patients undergoing sutureless laparoscopic partial nephrectomy. Methods There were 60 patients randomized into intervention and control groups. Ultrasound-guided posterior quadratus lumborum block was performed preoperatively using 30 ml 0.375% ropivacaine for patients in the intervention group. An ultrasound-guided posterior quadratus lumborum block was performed preoperatively using 30 ml 0.9% saline for patients in the control group. The primary outcomes included cumulative opioid consumption within 12 h postoperatively and quality of postoperative recovery at 48 h. Secondary outcomes included the Numerical Ration Scale (NRS) score, opioid consumption by time period, time to first pump compression, number of patients needing rescue analgesia, blood glucose and cortisol concentrations, early postoperative recovery indicators, and adverse events. Results There were 48 patients included in the final analysis. The intervention group had lower cumulative consumption of sufentanil within 12 h postoperatively and higher quality of postoperative recovery scores at 48 h postoperatively compared with the control group (p  0.001). The NRS at resting and movement of the intervention group was lower at 0 h, 6 h, and 12 h after surgery compared with the control group (p  0.05). At prespecified intervals (0 to 2 h, 2 to 6 h, 6 to 12 h, 12 to 24 h, and 24 to 48 h) after surgery, the intervention group had lower consumption of sufentanil compared with the control group (p  0.05). The intervention group took longer to press the analgesic pump for the first time within 48 h after surgery compared with the control group (p  0.001). The postoperative blood glucose and cortisol concentrations in the intervention group were lower than those in the control group (p  0.05). The times to first excretion, ambulation, and discharge were shorter in the intervention group compared with the control group (p  0.05). Conclusions The posterior quadratus lumborum block can be one of the best options for postoperative multimodal analgesia in patients undergoing sutureless laparoscopic partial nephrectomy.